Protocol for systematic review and meta-analysis for randomized clinical trials on patiromer efficacy and safety in subjects with heart failure. - Elnour, Asim Ahmed; Shehab, Abdulla (Pharmacy Practice (1886-3655))
Background: We shall assess the efficacy and safety of patiromer in subjects with heart failure (HF) in randomized controlled trials (RCTs). Methods: The protocol has been developed supported the PRISMA-P checklist by using (PICO [population, intervention, comparators, and outcome]) items, for adult subjects with HF who have received patiromer in RCTs versus SZC or placebo to attain specific endpoint of control of hyperkalemia. The subjects with HF (population) receiving patiromer (intervention) are compared to placebo or other potassium binders (comparators), like sodium zirconium cyclosilicate (ZS-9, SZC, Lokelma®) for the non-inferiority or superiority in terms of effects on hyperkalemia (outcome) and alter in potassium serum levels. Results: Patiromer may provide an efficient treatment for hyperkalemia in subjects with HF receiving angiotensin-converting enzyme inhibitor (ACEi), angiotensin receptor blocker (ARB) and/or mineralocorticoids/aldosterone antagonists (MRA/AA). Patiromer may facilitate the clinical utility of RAAS inhibitors without discontinuation or interruption of therapy in subjects with HF. Patiromer may enable dose titration of AA without the danger of hyperkalemia. Patiromer is anticipated to halt recurrence of hyperkalemia in subjects with HF. Conclusion: Patiromer may provide safe and effective therapy for prevention, maintenance, management, and prevent recurrence of hyperkalemia in subjects with HF as compared to the other comparators.